OpenMP: conquering the full hardware spectrum : 15th international workshop on OpenMP, IWOMP 2019, Auckland, New Zealand, September 11-13, 2019 : proceedings /: 15th international workshop on OpenMP, IWOMP 2019, Auckland, New Zealand, September 11-13, 2019 : proceedings. ([2019]) - Unknown
No abstract available